Finance and Development, June 1976. (Finance and Development; Finance and Development ;, 1976)
This paper highlights that in July 1975, an interdepartmental task force, chaired by the Director of the Bank's Transportation and Urban Projects Department, had been established to develop an 'urban poverty action program.' This task force published, in March 1976, an interim report containing tentative conclusions on the dimensions of the problem, and on the possible strategy the Bank might use to deal with urban poverty. The task force estimated that roughly 25 percent of the urban population of developing countries that are members of the Bank-some 150 million people-live in absolute poverty.